CRANIO VERTEBRAL FUNCTION ANOMALY WITH SPONDYLOSYNDESIS: A CASE REPORT (Journal of Pharmaceutical Negative Results, 2022)
Crania vertebral junction abnormalities such as at lantoaxial dislocation with or without basilar invagination with or without association chiari malformation may cause a high cervical myelopathy occasionally mechanical factor such as inadequate canal decompression torticollis and scoliosis may lead to lack of implement. A 30 years old male patient was admitted in the neuro ward with presenting complaint of weakness in right leg since 9 month, pain in neck region since 9 month, difficulty during walking and unable to climb stairs, tingling sensation in right hand since 9 month. After undergoing certain primary therapeutic investigation likeBlood investigation, MRI, x-ray, patientwas diagnosed with a Cranio Vertebral Function Anomaly.He was initially treated with antibiotics, penicillin, Analgesic, antacid, antiemetic, and intravenous fluid along with alternative therapies i.e. gropping exercises of upper limb, bed mobility training, bed side sitting, breathing exercise and dynamic quads.Patient showed progressive during hospitalization.